A confirmatory factor analysis and validation of the forms of self‐criticism/reassurance scale. (22nd August 2012) - Kupeli, Nuriye; Chilcot, Joseph; Schmidt, Ulrike H.; Campbell, Iain C.; Troop, Nicholas A.
<x xml:space="preserve">Abstract</x> Objective: Several studies have used the Forms of Self‐Criticism/Reassurance Scale (FSCRS; Gilbert, Clarke, Hempel, Miles, & Irons, 2004) when exploring the role of emotion regulation in psychopathology. However, psychometric evaluation of the FSCRS is limited. The present study sought to confirm the factor structure of the FSCRS based on theoretical and empirical grounds in a large sample of the general population. Method: The FSCRS was completed by a large sample of men and women (N= 1, 570) as part of an online survey. The data were randomly split in order to perform both independent exploratory (EFA) and confirmatory factor analyses (CFA). One‐, two‐ and three‐factor solutions were examined. Results: A three‐factor model of reassured‐self (RS) and the two types of self‐criticism, inadequate‐self (IS), and hated‐self (HS), proved to be the best‐fitting measurement model in this sample (χ2= 800.3, df= 148, p < .001; CFI [comparative fit index]= .966, TLI [Tucker Lewis index]= .961, RMSEA [root mean square error of the approximation]= .074). Although very similar to the original questionnaire, there were some differences in terms of the items that were retained. Validity was confirmed with the shortened FSCRS showing the same associations with mood and sex as the original version of the FSCRS. Conclusion: A three‐factor model (RS, IS and HS) provided the best‐fitting structure and confirmed the separation of different types of self‐criticism. Future research should explore the degree to which these separable aspects of self‐criticism are theoretically and clinically meaningful and to identify the role of self‐reassurance in ameliorating their effects. Practitioner Points Positive clinical implications The current paper has established that the FSCRS consists of self‐reassurance and two separable factors of self‐criticism (inadequate‐self and hated‐self). The current paper refined a measure to test the role of different kinds of self‐criticism in the aetiology of psychopathology as well as evaluate outcomes following intervention. Cautions and limitations The current study did not recruit a clinical sample and responses from a clinical group may have revealed a different factor solution. A high percentage of the sample was classed as 'white' and female so the results of this study may not be representative of the general population.